THE ILLEGALITY OF FRANCE’S EXPULSIONS OF BULGARIAN AND ROMANIAN ROMA UNDER EUROPEAN UNION LAW - Dimitrova, Silvia (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2013)
This contribution will try to answer the question whether and to what degree France has infringed domestic and European law by expulsing Romanian and Bulgarian Roma citizens since the acceptance of both countries into the European Union on January 1, 2007. This paper is divided in two parts. In the first part, the author seeks to demonstrate how the expulsions of Bulgarian and Romanian Roma citizens from France infringe the 2004 Directive on Freedom of Movement of European Union (EU) nationals under EU law. In the second part, the study shows that the curtailment of Bulgarian and Romanian citizens’ freedom of movement infringes those citizens’ rights under European law, namely under the European Social Charter and the European Convention on Human Rights. The rights discussed under the European Convention are the right to respect for private and family life under which is examined the right of housing and children’s right to education. Finally, the author outlines positive practices from France that can be translated into European Union law and adopted by the Member States as one means of ensuring Roma children’s right to education across the European Union.